2003
DOI: 10.1097/01.tp.0000053749.36365.7e
|View full text |Cite
|
Sign up to set email alerts
|

Indefinite islet protection from autoimmune destruction in nonobese diabetic mice by agarose microencapsulation without immunosuppression1

Abstract: Agarose microcapsules were able to completely protect NOD islet isografts from autoimmune destruction in the syngeneic islet transplantation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 28 publications
0
51
0
1
Order By: Relevance
“…When islet-containing droplets of sodium alginate solution are extruded from a needle and dropped into a divalent cation bath, they gel instantaneously, allowing the formed calcium alginate beads to retain the perfectly spherical shape that the alginate droplet had upon extrusion. Although the suitability of other polymers is still under investigation (e.g., agarose 20,21 ), none has been as extensively studied nor has reached the same level of performance as alginate. As a natural polymer, alginate is limited by its tendency to be largely contaminated.…”
Section: Introductionmentioning
confidence: 98%
“…When islet-containing droplets of sodium alginate solution are extruded from a needle and dropped into a divalent cation bath, they gel instantaneously, allowing the formed calcium alginate beads to retain the perfectly spherical shape that the alginate droplet had upon extrusion. Although the suitability of other polymers is still under investigation (e.g., agarose 20,21 ), none has been as extensively studied nor has reached the same level of performance as alginate. As a natural polymer, alginate is limited by its tendency to be largely contaminated.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, there are a number of achievements in encapsulating islets seen in small and large animal studies, as well as in early phase clinical trials. A syngeneic transplant of nonobese diabetic (NOD) into prediabetic islets diabetic NOD recipients, using 5% agarose encapsulating 1500-2000 islet equivalents (IEq), showed that intraperitoneal implantation as well as omental pouch transplants demonstrated prolonged euglycemia for a period of 100 days compared to 8 days for unencapsulated islet transplants [13]. This study was repeated in 2006, where the same period of normoglycemia was observed in transplant recipients.…”
Section: History Of Animal and Human Trials Of Islet Encapsulationmentioning
confidence: 87%
“…Åêñïåðèìåíòàëüíà àïðî-áàö³ÿ îòðèìàíèõ ðåçóëüòàò³â êóëüòèâóâàííÿ ñâ³ä-÷èòü ïðî ¿õ äîñèòü âèñîêó åôåêòèâí³ñòü [77][78][79][80][81].…”
Section: комбінована ксенотрансплантація як метод пролонгації життєздunclassified